Effectiveness of two retainer types in dental and occlusal stability - Gómez-Gómez, Sandra Liliana; Salazar-Quiceno, Luis Fernando; Guisao, Diego Alejandro; Betancur-Pérez, Jhon Jairo; Segura-Cardona, Ángela María (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: with the purpose of providing additional details on the selection of retainer type, this study sought to assess the stability of dental and occlusal position during retention phase using two types of retainers in individuals with no remnant growth who completed orthodontic treatment at the Universidad de Antioquia School of Dentistry, Universidad CES, and in private practice in Medellín in 2011. Methods: this was a controlled clinical study with a sample of 47 patients aged 15 to 45 years, randomly selected into two treatment groups: 22 patients with Essix retainer and 25 patients with Hawley plate in both arches. Cephalometric X-rays and study models were taken on all patients at baseline and six months later with monthly clinical evaluations. Results: the clinical and radiographic results showed significant differences in some tooth rotations in terms of upper intercanine distance and molar relationship, but overall there were no statistically significant differences between both retainers in the three space planes. Conclusions: there were no statistically significant differences between the retainers in a six-month evaluation period.